Life Skills Education Programs; The Bridge to the Employment of the Poors - Mulyadi, Didi; Rosyidi, Unifah; Suryadi, Suryadi (International Journal for Educational and Vocational Studies, 2019)
Employment is such kind of a very rare opportunity for the poors unable to attend formal schoolings. This research is examining the implementation effectiveness of skills based education program designed by the government through grant and scholarship to reduce the poverty and unemployment. It also tries to compare the design and its result to find whether the program was effectivey implemented or not. This research uses qualitative method through CIPP evaluation model. The research found that in a policy layer, context and input  evaluation steps, the life skills education program is comprehensively thought and considered as it covers aspects including the regulation, the program guidance, the fund aids, the curriculla, the guide for selected institutions ,the report mechanism. While at the process and product evalauation steps, the reserach found that there were huge gaps in implementation especially at the placement at the industries. There were only less than 10% of participants entering to work fields while most of its program participants work only as a parttimers which don’t provide reguler income,.So the target of decreasing the poverty and reducing the unemployment was not well measured.